2019
DOI: 10.15252/embr.201846989
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial AAA‐ATPase Msp1 detects mislocalized tail‐anchored proteins through a dual‐recognition mechanism

Abstract: The conserved AAA‐ATPase Msp1 is embedded in the outer mitochondrial membrane and removes mislocalized tail‐anchored (TA) proteins upon dysfunction of the guided entry of tail‐anchored (GET) pathway. It remains unclear how Msp1 recognizes its substrates. Here, we extensively characterize Msp1 and its substrates, including the mitochondrially targeted Pex15Δ30, and full‐length Pex15, which mislocalizes to mitochondria upon dysfunction of Pex19 but not the GET pathway. Moreover, we identify two new substrates, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 48 publications
(81 reference statements)
7
65
1
Order By: Relevance
“…This raises the question of how Msp1 recognizes its substrates in the OMM membrane. Recent analysis suggested the involvement of a juxtamembrane cytoplasmic hydrophobic patch in Pex15 is important for Msp1-mediated extraction (Li et al, 2019). However, Fmp32 and Gem1 do not show this feature (Figure 6—figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This raises the question of how Msp1 recognizes its substrates in the OMM membrane. Recent analysis suggested the involvement of a juxtamembrane cytoplasmic hydrophobic patch in Pex15 is important for Msp1-mediated extraction (Li et al, 2019). However, Fmp32 and Gem1 do not show this feature (Figure 6—figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies suggest that Msp1 is sufficient to extract TA proteins from proteoliposomes (Wohlever et al, 2017). Although these reconstitution experiments showed that the Msp1 N-terminal TM domain is dispensable for the dislocation reaction, recently Li et al suggested that a conserved negatively charged aspartate residue in the N-terminal portion of Msp1 facing the inter membrane space (IMS) is important for efficient recognition of Msp1 clients in vivo (Li et al, 2019). Moreover, a hydrophobic surface of the AAA-ATPase domain has been implicated in recognition of Msp1 clients (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, when ER membrane proteins are mislocalised, either to the mitochondria ( Figure 2 ) or the peroxisome, they are extracted and targeted for degradation by the hexametric ATPase Msp1 [ 15 , 16 ]. Recognition of such mislocalised substrates probably involves assessment of oligomeric state [ 17 , 18 ] and detection of characteristic hydrophobic and charged motifs adjacent to the transmembrane domain [ 19 ]. Substrates mistargeted to mitochondria are extracted by Msp1 near ER contact sites before ubiquitination and degradation at the ER membrane in a process involving the traditional ERAD components Doa10 and Cdc48 [ 17 , 20 , 21 ].…”
Section: Quality Control Of Organelle Targeting: Reading the Signals mentioning
confidence: 99%